Evaluating medical learners’ experiences with health literacy at a southeastern medical school - Faith Albertson; Ann Blair Kennedy; Shannon Stark Taylor; Nabil Natafgi (BMC Medical Education)
Abstract Background Health literacy (HL) is crucial for making informed health decisions. Over one-third of US adults have limited HL, leading to adverse health outcomes. Despite its importance, HL education lacks standardization in medical training. This study evaluates medical learners’ confidence and experiences with HL at the University of South Carolina School of Medicine Greenville’s (USCSOMG) and the Family Medicine Residency Program Greenville (FMRGVL) to propose recommendations for HL instruction. Methods A convergent parallel mixed methods design was used to assess the learners’ experiences with HL training through a student survey and faculty interviews. The study utilized thematic analysis for qualitative data and statistical analysis for quantitative data, focusing on prior and current HL training, confidence in HL application, and perceptions of HL education. Results The curriculum at USCSOMG and FMRGVL incorporate active learning strategies, emphasizing HL and patient communication. Most participants reported high confidence in their HL knowledge and skills. The preferred teaching methods were hands-on clinical interactions, observing clinical interactions, and interactive lessons. Barriers to using HL interventions included time constraints and lack of real-world experience. Faculty recommended time prioritization and collaborative strategies to overcome these barriers. Conclusions This study highlights the impact of curricular approaches at USCSOMG and FMLGVL on learners’ confidence in engaging with patients facing low health literacy (LHL). To overcome barriers like time constraints and real-world challenges, medical educators should consider implementing competency-based exams, increasing practical opportunities for health literacy skills, and incorporating continuous curriculum evaluation based on faculty and student feedback. HL training and evaluation are essential to ensure that medical learners are adequately prepared to meet diverse patient literacy needs. Clinical Trial Number: Not Appliable